Role of virtual bronchoscopy in children with a vegetable foreign body in the tracheobronchial tree. Issue 12 (December 2014) - Behera, G; Tripathy, N; Maru, Y K; Mundra, R K; Gupta, Y; Lodha, M
Abstract Objectives: Multidetector computed tomography virtual bronchoscopy is a non-invasive diagnostic tool which provides a three-dimensional view of the tracheobronchial airway. This study aimed to evaluate the usefulness of virtual bronchoscopy in cases of vegetable foreign body aspiration in children. Methods: The medical records of patients with a history of foreign body aspiration from August 2006 to August 2010 were reviewed. Data were collected regarding their clinical presentation and chest X-ray, virtual bronchoscopy and rigid bronchoscopy findings. Cases of metallic and other non-vegetable foreign bodies were excluded from the analysis. Patients with multidetector computed tomography virtual bronchoscopy showing features of vegetable foreign body were included in the analysis. For each patient, virtual bronchoscopy findings were reviewed and compared with those of rigid bronchoscopy. Results: A total of 60 patients; all children ranging from 1 month to 8 years of age, were included. The mean age at presentation was 2.01 years. Rigid bronchoscopy confirmed the results of multidetector computed tomography virtual bronchoscopy (i.e. presence of foreign body, site of lodgement, and size and shape) in 59 patients. In the remaining case, a vegetable foreign body identified by virtual bronchoscopy was revealed by rigid bronchoscopy to be a thick mucus plug. Thus, the positive predictive value of virtual bronchoscopy was 98.3 per cent. Conclusion: Multidetector computed tomography virtual bronchoscopy is a sensitive and specific diagnostic tool for identifying radiolucent vegetable foreign bodies in the tracheobronchial tree. It can also provide a useful pre-operative road map for rigid bronchoscopy. Patients suspected of having an airway foreign body or chronic unexplained respiratory symptoms should undergo multidetector computed tomography virtual bronchoscopy to rule out a vegetable foreign body in the tracheobronchial tree and avoid general anaesthesia and invasive rigid bronchoscopy.